Belief toward patient with mental health problem among medical doctors in Hospital Universiti Sains Malaysia - Azim, Nur Syamimi Che Md (2020)
BACKGROUND Doctors play an important role to treat patients with mental illness. Doctor’s negative belief towards patients with mental illness could affect the quality of care to their patients. However, there is limited research related to belief towards mental illness among doctors. Therefore, the objective of this study is to determine the level of belief among medical doctors in HUSM about dangerousness, social dysfunction, incurability, embarrassment as well as its associated factors. METHODOLOGY A cross-sectional study was conducted among 180 medical doctors in Hospital Universiti Sains Malaysia from January 2020 to May 2020. The respondents were recruited using purposive sampling. They were required to complete a set of online self-administered questionnaires including sociodemographic profile and Belief toward Mental Illness Scale (BTMI) which was distributed through email and personal message. The data was analysed using the IBM SPSS Statistical Software Version 24. RESULTS The mean years of experience among the participants were 7.39 (5.46). Medical officers were the group that mostly responded, 111 (66.2%). Most of them from the non-psychiatry department compared to psychiatry, 162 (90.0%) but the distribution of participants from all department was evenly distributed. About 33.9% had psychiatry experience and the majority had past contact with a patient with mental health problem 155 (86.1%) and 14.4% of the participants had experienced mental health problems. The mean scores of belief among medical doctors were relatively low with a mean value of 43.32 (14.74). All four subscale also showed low mean value with dangerousness 6.95 (3.94), social dysfunction 14.08 (5.68), incurability 14.37 (4.7), and embarrassment 7.92 (4.01). There were significant associations observed between doctors working in the psychiatry department with dangerousness, social dysfunction, and embarrassment subscale, where they have a lower score in the three subscales. There was also a significant association between Indian ethnicity and incurability, where they score lower in the incurability subscale. CONCLUSION In this study, we found doctors hold positive beliefs toward patients with mental health problems regardless of their sociodemographic background. There was a better belief about dangerousness, social dysfunction, and embarrassment among medical doctors from the psychiatry field.